Viscosity behavior of polymeric flocculant solutions - C. Rattanakawin (2018)
Viscosity measurements of polymeric flocculant solutions of poly-dimethyldiallylammonium chloride (DMDAAC) and poly-acrylamide/acrylic acid (AM/AA) families at various concentrations and solution chemistry have been carried out using the Cannon-Fenske routine viscometer. In this study, the viscosity behavior of these polymer solutions is described in terms of reduced viscosity. From the reduced viscosity-polymer concentration (ηred-C) plot, the linearity of the viscosity behavior is observed for the nonionic polymer (poly-AM). The nonlinear behavior of the ionic polymer solutions of the cationic (poly-DMDAAC) and the anionic (poly-AM/AA) obtained from this study is the result of electroviscous effects. For the cationic polymer solutions, the polymer concentration (C) and molecular weight (MW) dependence of the viscosity results mainly from the second-order electroviscous and hydrodynamic effects, respectively. Ionicity dependence of the viscosity of the anionic polymer solution may be attributed to the second-order electroviscous effect. The effect of solution pH and electrolyte addition using sodium chloride on the viscosity of charge type polymer solutions is due to the third-order electroviscous effect. The hydrodynamic and electroviscous effects will be discussed in detail. © 2007 Elsevier Ltd. All rights reserved.